Kajian Hukum Perikatan sebagai Alat Perlindungan bagi Pihak dalam Perjanjian Bisnis di Indonesia - Putri Nadila Asrizal; Satria Akbar; Yola Anika (Program Studi Ilmu Hukum, Universitas Kuningan, 2024)
Economic growth of citizens in Indonesia is increasingly growing especially in transactions of sale and sale through electronic media, so that there needs to be some legal protection against consumers linked to the transaction. The aim of this research is to learn about the validity of an electronic transaction in Indonesia and how it is protected by law. This research uses an empirical jurisprudence method, which is a study that uses data from libraries such as legislative regulations, books, legal journals, and scientific works related to this research. There is also the result of this research is that the Preliminary, some validity of the Agreement to protect the parties involved in a broader business agreement, including consumers and producers who are outside the territory of the Republic of Indonesia has been regulated in Article 18 Paragraph (1) of the Consumer Protection Act, as well as the Second, the regulation of the use of information technology and communications in business transactions, including legal protection for the parties concerned in accordance with the legislative regulations of the invitation No. 82 Year 2012 on the maintenance of systems and electronic transaction.